1975
DOI: 10.1207/s15327906mbr1004_5
|View full text |Cite
|
Sign up to set email alerts
|

Conjoint Psychotherapeutic Experience: Some Dimensions and Determinants

Abstract: In our previous reports we have specified the empirical structure of patients' and therapists' experiences in psychotherapeutic sessions. The present report explores the structure of experience within the therapeutic dyad -- conjoint experience. Seven factors were derived from the reports of 28 patient-therapist pairs. One factor reflected the therapist's approach to his role as a help-giver, and another reflected the patient's approach to her role. Other patterns showed convergent perceptions, while still oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
73
0

Year Published

1986
1986
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(75 citation statements)
references
References 0 publications
2
73
0
Order By: Relevance
“…In terms of congruence with the client experiencing literature, the changes Ms. K described as a result of treatment reflect those cited in many previous studies: improved interpersonal functioning and self-esteem, reduced anxiety, greater mastery (Strupp et al, 1969), self-understanding and awareness, relief (Elliott & James, 1989), empowerment and personal contact with the therapist (Timulak, 2007). Likewise, the change mechanisms that Ms. K described in her posttermination interview reflected the “helpful experiences” or “impacts” reported by previous researchers: involvement with an emotionally present therapist, insight/introspection, greater understanding of the self in relation to others, catharsis, confidence, relief, feeling understood, and so on (Elliott et al, 1985; Elliott & James, 1989; Orlinsky & Howard, 1975; Timulak, 2007).…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…In terms of congruence with the client experiencing literature, the changes Ms. K described as a result of treatment reflect those cited in many previous studies: improved interpersonal functioning and self-esteem, reduced anxiety, greater mastery (Strupp et al, 1969), self-understanding and awareness, relief (Elliott & James, 1989), empowerment and personal contact with the therapist (Timulak, 2007). Likewise, the change mechanisms that Ms. K described in her posttermination interview reflected the “helpful experiences” or “impacts” reported by previous researchers: involvement with an emotionally present therapist, insight/introspection, greater understanding of the self in relation to others, catharsis, confidence, relief, feeling understood, and so on (Elliott et al, 1985; Elliott & James, 1989; Orlinsky & Howard, 1975; Timulak, 2007).…”
Section: Discussionmentioning
confidence: 65%
“…In the literature on transtheoretical change mechanisms, there has been a fair amount of research on what clients see as therapeutic. Pioneering studies were published by Snyder (1961); Strupp, Fox, and Lesser (1969); Orlinsky and Howard (1975); and Elliott, James, Reimshuessel, Cislo, and Sack (1985). Elliott and James's (1989) review of studies on client experiencing concluded that whether the unit of analysis was the session, an event within a session, or the whole treatment, clients' reports of therapeutic impact reflect the experience of help or relief within the therapeutic relationship as well as the accomplishment of tasks.…”
mentioning
confidence: 99%
“…Whereas in the 60s, therapy process measures were on Strupp's “wish list,” at the end of the first decade of the 21st century, there is likely an overabundance of these types of instruments. In my own field of interest, therapy relationship, the first measures came online in the mid 70s, starting with the pioneering work of Orlinsky and Howard (1975), Barrett-Lennard (1978), and Alexander and Luborsky (1987). By a recent count, there were more than 60 measures of the alliance alone (Elvins & Green, 2008; Horvath, 2011b).…”
Section: Methodsmentioning
confidence: 99%
“…To facilitate the adaptation and participation of the group members, each session started with one of eight video films of 20-30 min duration. Eight themes were selected in accordance with Orlinsky & Howard (1975). The videos were shown in the following order: personal relations, work, religion, alcoholism, family relations, sexuality, violence and honesty.…”
Section: Methodsmentioning
confidence: 99%